2003
DOI: 10.1021/jp030557b
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Ice Particles from a Graphite Surface:  A Molecular Dynamics Simulation Study

Abstract: Large-scale classical trajectory calculations of (H 2 O) n , n e 25 159, colliding with a graphite surface have been carried out in order to relate the phenomenon of direct scattering to the initial conditions of the collision. The collisions were performed at normal incidence with the incident velocity ranging from 50 to 2000 ms -1 and at surface temperatures between 300 and 1400 K. Upon impact, the cluster is deformed elastically (reversibly) and plastically (irreversibly), and if the elastically stored ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…This behavior can be explained by the observation that formation of charged clusters mainly is associated with evaporationmediated cluster emission. 28 Figure 4͑d͒ shows the final kinetic energy distributions in the scattered flux for incident beams with different average cluster sizes. As expected, the final kinetic energy increases with increasing incident cluster size.…”
Section: B Kinetic Energy Distributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…This behavior can be explained by the observation that formation of charged clusters mainly is associated with evaporationmediated cluster emission. 28 Figure 4͑d͒ shows the final kinetic energy distributions in the scattered flux for incident beams with different average cluster sizes. As expected, the final kinetic energy increases with increasing incident cluster size.…”
Section: B Kinetic Energy Distributionsmentioning
confidence: 99%
“…We recently reported that in addition to the evaporation-mediated emission of cluster fragments, large water clusters may also undergo direct inelastic scattering. 28 The evaporation-mediated process was present at surface temperatures above 700 K, while direct scattering of clusters was observed also at lower surface temperatures.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations